Assessment of risk factors for hypertension among undergraduate students in a medical college of Himachal Pradesh, India - Pathania, Shamli; Sharma, Shruti; Sharma, Sumit; Kumar, Arvind; Thakur, Shishu Pal Singh (International Journal Of Community Medicine And Public Health, 2024)
Background: Hypertension is a commonest cardiovascular disorder and is major cause of premature death worldwide. An estimated 1.28 billion adults aged 30-79 years worldwide have hypertension, most (two-thirds) living in low and middle-income countries. So present study was undertaken to assess the risk factors for hypertension among First year MBBS students so that suitable preventive measures may be undertaken. Methods: It is cross sectional study conducted among first year MBBS students in DRKGMC Hamirpur. The duration of study is three months. The tools of study used were modified structured pretested self-administered questionnaire; WHO stepwise approach to chronic disease risk factor surveillance (STEPS). Weighing machine, measuring tape, digital BP apparatus and steadiometer. Results: A total of 115 students of MBBS first year participated in the study. There were a total of 31.3% (36) boys and 68.7% (79) girls. Thirty three percent (38) had a family history of hypertension. 16.52% (19) had a BMI more than the normal. Among the study participants only 5 students (4.35%) used to consume alcohol and smoke cigarettes. Most of study participants consume fast food and junk food. Conclusions: High prevalence of different modifiable risk factors for hypertension revealed among the study subjects.There is need to screen the modifiable risk factors from very early age.